New textile for personal protective equipment—plasma chitosan/silver nanoparticles nylon fabric - Botelho, C. M. (2021)
Fabric structures are prone to contamination with microorganisms, as their morphology and ability to retain moisture creates a proper environment for their growth. In this work, a novel, easily processed and cheap coating for a nylon fabric with antimicrobial characteristics was devel- oped. After plasma treatment, made to render the fabric surface more reactive sites, the fabric was impregnated with chitosan and silver nanoparticles by simply dipping it into a mixture of different concentrations of both components. Silver nanoparticles were previously synthesized using the Lee–Meisel method, and their successful obtention was proven by UV–Vis, showing the presence of the surface plasmon resonance band at 410 nm. Nanoparticles with 25 nm average diameter observed by STEM were stable, mainly in the presence of chitosan, which acted as a surfactant for silver nanoparticles, avoiding their aggregation. The impregnated fabric possessed bactericidal activ- ity higher for Gram-positive Staphylococcus aureus than for Gram-negative Pseudomonas aeruginosa bacteria for all combinations. The percentage of live S. aureus and P. aeruginosa CFU was reduced to less than 20% and 60%, respectively, when exposed to each of the coating combinations. The effect was more pronounced when both chitosan and silver were present in the coating, suggesting an effective synergy between these components. After a washing process, the antimicrobial effect was highly reduced, suggesting that the coating is unstable after washing, being almost completely removed from the fabric. Nevertheless, the new-coated fabric can be successfully used in single-use face masks. To our knowledge, the coating of nylon fabrics intended for face-mask material with both agents has never been reported.